2017
DOI: 10.1002/humu.23202
|View full text |Cite
|
Sign up to set email alerts
|

A variant in acis-regulatory element enhances claudin-14 expression and is associated with pediatric-onset hypercalciuria and kidney stones

Abstract: The greatest risk factor for kidney stones is hypercalciuria, the etiology of which is largely unknown. A recent genome-wide association study (GWAS) linked hypercalciuria and kidney stones to a claudin-14 (CLDN14) risk haplotype. However, the underlying molecular mechanism was not delineated. Recently, renal CLDN14 expression was found to increase in response to increased plasma calcium, thereby inducing calciuria. We hypothesized therefore that some children with hypercalciuria and kidney stones harbor a CLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
(39 reference statements)
0
19
1
Order By: Relevance
“…However, in vivo experiments are required to validate this in silico hypothesis. A previous in silico study hypothesized that rs78250838 might introduce a new transcription factor binding site within CLDN14, but this SNP was not associated with calcium excretion in our patients and was not in linkage with rs219780 and rs219755 (35).…”
Section: Discussioncontrasting
confidence: 55%
“…However, in vivo experiments are required to validate this in silico hypothesis. A previous in silico study hypothesized that rs78250838 might introduce a new transcription factor binding site within CLDN14, but this SNP was not associated with calcium excretion in our patients and was not in linkage with rs219780 and rs219755 (35).…”
Section: Discussioncontrasting
confidence: 55%
“…In another study with 200 kidney SF and 200 healthy controls from the eastern part of India, the two variants rs219777 and rs219778 in the CLDN14 gene were found to be strongly associated with kidney stone disease, but no significant association was found with urinary or serum Ca [86]. A more recent study described the association of the CLDN14 gene variant rs78250838:C>T in an intronic cis-regulatory element with early-onset hypercalciuria and kidney stones in children [87]. In vitro studies revealed that this variant enhances claudin-14 expression, thereby increasing urinary Ca excretion and promoting calcium stone formation.…”
Section: Claudin-14mentioning
confidence: 98%
“…Wild type littermate sections were taken as a negative control. Then, sections were rinsed with PBS twice for 5 min before mounting with DAKO (Carpinteria, CA, USA) or undergoing immunostaining, essentially as previously reported [19,32]. In brief, antigen retrieval was performed with sodium citrate, and then washed three times with TN buffer (0.1 M Tris/HCl and 0.15 M NaCl, pH 7.6).…”
Section: X-gal Staining and Immunofluorescence Microscopy On Renal Sementioning
confidence: 99%